A possible Tsunami deposit associated to the CE 1755 Lisbon earthquake on the Western Coast of Portugal - Tudor, Mihaela (2020)
The CE 1755 Lisbon tsunami was the largest historical tsunami to affect the Atlantic coasts of Europe and North Africa. This study presents the results obtained from the application of different sedimentological techniques (e.g., grain size, morphoscopy, microtextural analysis, geochemistry, radiocarbon dating) on sediments retrieved from the Alcabrichel River alluvial plain (of about 500 m far away from its mouth and approximatively 50 km northwest of Lisbon, Portugal). The results allowed the identification of a sandy layer that was associated with the CE 1755 tsunami. Furthermore, a new microtextural semi-quantitative classification was applied to enhance the identification of extreme marine inundation deposits. Based on sedimentological data, three different tsunami inundation phases were identified, including two inundations and a likely backwash. This innovative work offers physical evidence of the spatial presence of the CE 1755 tsunami event on the western coast of Europe. It also enables a reconstruction of tsunami inundation dynamics, with two flooding waves and an interspersed backwash.